Search for CP Violation through the Dₛ⁺ → K⁻ K⁺ K⁺ decay in the LHCb Experiment - Pachas Clemente, Javier Alejandro (2015)
This dissertation aims to report the search for charge-parity (CP) violation in the singly-Cabibbo-suppressed decay Dₛ⁺ → K⁻ K⁺ K⁺ at the LHCb Experiment (CERN). According to the Standard Model, direct CP violating asymmetries in charm decays can occur but only up to the order of 10⁻³ or less. If asymmetries at the percent level are found, new CP violation mechanisms beyond the Standard Model are necessary. A model- independent technique known as the Mirandizing method is performed to look for local charge asymmetries in the phase space (the so-called Dalitz plot), of the decay Dₛ⁺ → K⁻ K⁺ K⁺. Our final data sample consists of over 50 thousand events collected in 2012 by the LHCb experiment from proton-proton collisions at a center-of-mass energy of 8 TeV. This is the first time that such analysis is performed to this channel. To guarantee that no nuisance asymmetries appear due to other sources such as background, production or detection effects, the study is first performed to the mass sidebands of the signal as well as to two control channels, D⁺ → K⁻ π⁺ π⁺ and Dₛ⁺ → K⁻ K⁺ π⁺, for which no CP violating asymmetries are expected since they are Cabibbo-favored decays. We then analyze the signal sample to find that, under the current statistics, there is no sign of CP violation in the Dₛ⁺ → K⁻ K⁺ K⁺ decay.